Experimental and finite element analysis of doubly reinforced concrete slabs subjected to blast loads. (January 2015) - Thiagarajan, Ganesh; Kadambi, Anirudha V.; Robert, Stephen; Johnson, Carol F.
Abstract: This paper presents research on the response and behavior of both high strength concrete (107 MPa) and normal strength concrete (27.6 MPa) slabs doubly reinforced with high strength low alloy vanadium (HSLA-V) reinforcement (VR) and conventional steel reinforcing bars (NR) subjected to explosive loads. Four types of reinforced concrete (RC) slabs namely High Strength Concrete (HSC) with HSLA-V Steel Reinforcing bars (HSC-VR), High Strength Concrete with Conventional Steel Reinforcing bars (HSC-NR), Normal Strength Concrete (NSC) with HSLA-V Steel Reinforcing bars (NSC-VR), and Normal Strength Concrete with Conventional Steel Reinforcing bars (NSC-NR) have been studied and compared both experimentally and numerically. The slabs were subjected to blast loads using a shock tube capable of generating both positive and negative phase pressures. Data collected during the dynamic experiments consisted of reflected pressure obtained from several pressure gages arranged along the perimeter of the test article and mid-span deflections captured from an accelerometer, a laser device, and high speed video. The numerical analysis was performed with the commercial program LS-DYNA using two material models. The concrete material models considered were Winfrith Concrete Model (WCM) and Concrete Damage Model Release 3 (CDMR3). Results from the numerical simulation are compared with the experimental values to determine material parameters and other finite element model related constraints. Mesh sensitivity and crack propagation studies were also conducted. From this study it was observed that CDMR3 and WCM can be used over a wider range of concrete compressive strengths. The advantages and disadvantages of using high strength materials are discussed. Highlights: Experimental data from uniform blast loading on doubly reinforced concrete slabs presented. Comparison of performance of combination of slabs made of high strength concrete and steel. Finite element analysis using two concrete models in LSDYNA gave good comparison with deflection data. High strength concrete was very effective in reducing the level of response. Default material models with default properties can be used to reasonably predict the response of such slabs.